The processing of typological similar languages among trilingual speakers of Spanish, English and Portuguese - Forcelini, Jamile (2020)
Research shows (VAN HESTE, 1999; VAN HELL; DE GROOT, 1998; VAN HEUVEN, DIJSTRA; GRAINGER, 1998) that when bilinguals process words in one language, shared word features from both languages are also activated. Most lexical processing studies have examined word processing among bilinguals and a smaller subset of studies have focused on word processing among trilinguals. The present study investigates how native and heritage trilingual Spanish speakers process words in comparison to non-native trilingual Spanish speakers. A  group of native and heritage trilingual Spanish speakers (n=26) (L1-Spanish, L2-English and L3-Portuguese) and a group of non-native trilingual Spanish speakers (n=40) (First Language (L1) English, Second Language (L2) Spanish and Third Language (L3) Portuguese) visually processed words in different languages (Spanish, Portuguese, German and Basque)  and had to determine whether the words they saw were real Spanish words. Reaction times and accuracy were analyzed among both groups and across word type. The goal was to test whether the presence of a third language such as Portuguese would affect processing in a previous known language (first or second language-Spanish). All participants included in this study were at the beginning stages of learning Portuguese as a third language. Results show native/heritage trilingual speakers were able to process words in Spanish faster than nonnative trilingual speakers in addition to processing all word types (in Portuguese, Spanish, German and Basque) more accurately as well. The present findings are analyzed in light of Dijkstra and Van Heuven’s (2002) Bilingual Interactive Activation Plus model of word recognition (BIA+).